Effect of Waste Palm Oil Reclaiming Agent on Viscoelastic and Mechanical Properties of Hot-in-Place Recycled Mixture - Xuekai Gao; Fansheng Kong; Huailei Cheng; Yancong Zhang; Chenyang Xue; Zhiqiang Cheng (Applied Sciences)
A new type of reclaiming agent was prepared by adding a plasticizer and an anti-aging agent to waste palm oil. A dynamic shear rheological test, bending beam rheological test, dynamic modulus test, static creep test, and road performance test were used to compare and analyze the viscoelastic characteristics of vegetable oil (WPO) and a traditional petrochemical reclaiming agent (PCO). The results showed that the WPO has better low-temperature crack resistance compared with the PCO, and the optimal dosage is about 12% of the mass fraction of aged asphalt. The addition of a regenerator reduces the dynamic modulus of the reclaimed asphalt mixture (RAP) under study and increases the phase angle. The improved CAM model showed good fit with the dynamic modulus and phase angle of recycled asphalt mixtures with the development of frequency. When the loading frequency was higher than 10 Hz, the dynamic modulus of the waste palm oil recycled asphalt mixture was lower, and the phase angle was higher. Conversely, when the loading frequency was lower than 0.01 Hz, the waste palm oil regenerant showed better temperature sensitivity. The waste palm oil recycled asphalt mixture demonstrated a higher steady creep rate and strain magnitude, lower stress relaxation time, and higher dissipation energy ratio under low-temperature conditions, thus improving the low-temperature crack resistance. Furthermore, the road performance test results of the asphalt mixtures indicated that the waste palm oil reclaimed asphalt mixture has excellent high-temperature rutting resistance, low-temperature cracking resistance, and water damage resistance, which confirms the reliability of the above analysis results. Therefore, the waste palm oil regenerant has great potential application prospects with wide source availability, low price, and outstanding mechanical properties.